Impact of the coronavirus 2019 (COVID-19) pandemic on anxiety diagnosis in general practices in Germany. (November 2021) - Jacob, Louis; Smith, Lee; Koyanagi, Ai; Oh, Hans; Tanislav, Christian; Shin, Jae Il; Konrad, Marcel; Kostev, Karel
Abstract: Little is known about the effects of the coronavirus disease-2019 (COVID-19) pandemic on the diagnosis of anxiety disorder. Therefore, the goal of this study was to compare the number of adults with a diagnosis of anxiety disorder and the number of adults newly diagnosed with anxiety disorder in Germany between January–June 2019 and January–June 2020, and to identify potential differences in terms of sociodemographic characteristics, prescriptions and comorbidities between these patients. The study included patients with at least one consultation in one of 1140 general practices in Germany in January–June 2019 and January–June 2020. Sociodemographic characteristics included age and sex, while there were three families of drugs and nine common comorbidities available for the analysis. An increase in the number of patients with anxiety disorder was observed in 2020 compared with 2019 (January: +4%, p = 0.643; February: +4%, p = 0.825; March: +34%, p < 0.001; April: +8%, p = 0.542; May: +2%, p = 0.382; June: +19%, p = 0.043; and March–June: + 19%, p < 0.001). There was also an increase in the number of patients newly diagnosed with anxiety disorder between March–June 2020 and March–June 2019 (11, 502 versus 9506; +21%, p-value<0.001). Antidepressants, anxiolytics and herbal sedatives were less frequently prescribed in patients newly diagnosed with anxiety disorder in 2020 than in 2019 (30.4% versus 35.6%, p-value<0.001). Finally, COPD (9.4% versus 7.9%, p-value<0.001) and asthma (11.3% versus 9.7%, p-value<0.001) were more frequent in 2020 than in 2019. Taken these findings together, public health measures are urgently needed to mitigate the negative impact of the COVID-19 pandemic on anxiety disorder.